DISTRAKSI DIGITAL DAN PENURUNAN KONSENTRASI BELAJAR SISWA SEKOLAH DASAR ISLAM - Muhammad Alfi Syahrin; Dody Tisna Amijaya; Rifqi Khoiril Anam; Rani Asmara (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Digital distraction has become one of the major challenges in learning within the era of digital transformation, potentially reducing students’ learning concentration. The increasing use of smartphones, social media, digital applications, and technology-based learning platforms has created a learning environment filled with stimuli that can divert students’ attention from academic activities. This study aims to analyze the forms of digital distraction, contributing factors, impacts on learning concentration, and mitigation strategies within educational settings, particularly among Islamic elementary school students. This research employed a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. A total of 33 Scopus-indexed articles published between 2022 and 2026 were analyzed using thematic content analysis. The findings reveal that the most common forms of digital distraction include social media, application notifications, smartphones, digital gaming, and multitasking activities. The causes of digital distraction stem from technological, individual, and learning-environment factors. Digital distraction negatively affects learning concentration, increases cognitive load, reduces academic engagement, and lowers the quality of learning comprehension. Effective mitigation strategies include strengthening self-regulated learning, enhancing digital literacy, optimizing the roles of teachers and parents, and implementing interactive and engagement-oriented learning approaches. This study highlights that the wise management of technology is essential for maintaining students’ learning concentration while supporting character development and learning ethics within Islamic elementary school education. Keywords: digital distraction; learning concentration; Islamic elementary school; digital literacy; systematic literature review.